DSL Composition for model-based test generation - Barroca, Bruno; Lucio, Levi; Amaral, Vasco; Pedro, Luis; Buchs, Didier (Electronic Communications of the EASST, 2009)
Domain specific languages (DSL) which describe reactive systems generally have a need for systematic generation of tests for their models. During the design of a DSL there is a lack of support for its integration with existing model based test generation tools. In this paper, we show how this integration can be conceptualized and systematized. We introduce a framework for composing DSLs for reactive systems, with a particular DSL for Model Based Testing called SATEL (Semi-Automatic Testing Language). This DSL composition is achieved by composing both the syntaxes of the two DSLs and their semantics. The result of this composition is also a language where it is possible to express models in the target DSL and test specifications for those models. The semantics of the composed language corresponds to the generation of test cases for models expressed in the target DSL. We finish the paper by analyzing the compositional framework we obtained in terms of its applicability to other target DSLs.